Sorting Gold and Sand (Silica) Using Atomic Force Microscope-Based Dielectrophoresis - Kim, Chungman; Hong, Sunghoon; Shin, Dongha; An, Sangmin; Zhang, Xingcai; Jhe, Wonho (Nano-Micro Letters, 2021)
Additive manufacturing–also known as 3D printing–has attracted much attention in recent years as a powerful method for the simple and versatile fabrication of complicated three-dimensional structures. However, the current technology still exhibits a limitation in realizing the selective deposition and sorting of various materials contained in the same reservoir, which can contribute significantly to additive printing or manufacturing by enabling simultaneous sorting and deposition of different substances through a single nozzle. Here, we propose a dielectrophoresis (DEP)-based material-selective deposition and sorting technique using a pipette-based quartz tuning fork (QTF)-atomic force microscope (AFM) platform DEPQA and demonstrate multi-material sorting through a single nozzle in ambient conditions. We used Au and silica nanoparticles for sorting and obtained 95% accuracy for spatial separation, which confirmed the surface-enhanced Raman spectroscopy (SERS). To validate the scheme, we also performed a simulation for the system and found qualitative agreement with the experimental results. The method that combines DEP, pipette-based AFM, and SERS may widely expand the unique capabilities of 3D printing and nano-micro patterning for multi-material patterning, materials sorting, and diverse advanced applications. Highlights: 1 The dielectrophoresis-based platform combined with micropipette-based atomic force microscope is demonstrated for material- and position-selective deposition. 2 The feasibility of on-demand sorting and printing using multi-materials in the single reservoir through a (sub)-microscale nozzle in the ambient condition is presented.